APOE‐ε4 shapes temporo‐parietal network properties in middle‐aged, cognitively unimpaired individuals: A graph theory analysis: Neuroimaging / imaging and genetics. (7th December 2020) - González‐de‐Echávarri, José Maria; Cacciaglia, Raffaele; Falcon, Carles; Sánchez‐Benavides, Gonzalo; Suárez‐Calvet, Marc; Milà‐Alomà, Marta; Arenaza‐Urquijo, Eider M; Grau‐Rivera, Oriol; Operto, Greg; Vilor‐Tejedor, Natalia; Sala‐Vila, Aleix; Crous‐Bou, Marta; et al.
Abstract: Background: The allele ε4 of the APOLIPOPROTEIN E gene ( APOE‐ε4 ) is the strongest genetic risk factor for sporadic Alzheimer's disease (AD). However, the underlying mechanisms are not well understood. Our objective was to assess the effect of the APOE ‐ ε4 allele dose on brain functional connectivity networks in cognitively unimpaired middle‐age individuals, using resting‐state functional magnetic resonance imaging (rs‐fMRI) and graph theory. Method: This research included resting state 3 tesla functional Magnetic Resonance Imaging (rs‐fMRI) data from 349 cognitively unimpaired subjects from the ALFA+ cohort study, in which clinical, genetic and AD core cerebrospinal fluid biomarkers (Aβ42 and p‐tau), measured using Elecsys® immunoassays (Roche Diagnostics) data were also collected. The sample was composed of 127 men and 222 women with a mean age of 60.2 years, 32 homozygous ε4, 123 heterozygous ε4 and 164 non‐carriers. The CONN toolbox (matlab toolbox) was used to preprocess and analyze the fMRI images with the default pipelines and adjusting by age, sex and years of education. ROI‐to‐ROI bivariate correlations were performed using cortical ROIs of Harvard‐Oxford atlas to compute each subject adjacency matrix. After thresholding and binarizing these results, graph theory was used to analyze the differences between APOE‐ε4 groups and false discovery rate (p‐FDR= 0.05) was applied. Results: We observed APOE‐ε4 allele‐dose dependent effects on multiple network properties, including reduced degree centrality, reduced global efficiency and increased average path length located in temporo‐parietal nodes: left temporo‐occipital fusiform cortex, occipital fusiform gyrus, right lateral parietal cortex, temporal pole and posterior superior temporal gyrus. In addition, increased betweenness centrality of the precuneus was also observed. (Figure 1). These results survived after adjusting the model for Aβ42 and p‐tau values. Conclusion: APOE‐ε4 allele modulates the functional integration among cortical nodes within temporo‐parietal networks, which typically present structural and metabolic alterations in AD. Importantly, these effects survived after adjustment by AD core biomarkers, suggesting that they were selectively mediated by APOE genotype. The inclusion of neuropsychological data shall clarify whether this distinctive network configuration may represent a network vulnerability or underlie compensatory strategies.